The frequency of hospital-acquired infections in Mousavi Hospital Zanjan, Iran - Kamali Aghdam, Mojtaba; Sadeghzadeh, Mansour; Fallah, Ramezan; Motamdinasab, Elaheh (International Journal of Infection Control, 2016)
Hospital-acquired infections occur in 5 to 10% of admitted patients in hospital. It is one of the main reasons for death of many hospitalized patients especially in developing countries. Therefore, finding ways to control these infections should be a priority and certainly the first step in achieving this goal. The aim of this study was to determine the frequency of hospital-acquired infections and related factors in Mousavi Hospital in Zanjan, Iran. The demographic data and data about the kind of infection, admission, duration and the ward of admission were reviewed. Statistical analysis was performed by SPSS version 16.0. Among 34102 admitted patients from 21st March 2013 to 21st March 2014 in Mousavi hospital in Zanjan, Iran, 206 (0.6%) patients, 141 (68.4%) male and 65 (31.6%) female, met the criteria of hospital-acquired infections. The highest frequency was in the burn ward with 82 (20.55%) patients. The most common type of infections were surgical site infections, pneumonia, urinary tract infection, sepsis and eye infection respectively. There was a significant correlation between the type of hospital-acquired infections and hospital wards (P=0.0001). The rate of hospital-acquired infections in this study is lower than other studies, which can be due to an effective way of infection control with continuous surveillance and health education for hospital staffs. However, poor diagnostic methods and failure in the reporting system of infections should be considered.